2019
DOI: 10.3390/met9020152
|View full text |Cite
|
Sign up to set email alerts
|

Effect of SiO2 on the Mechanical Property and Reduction of Calcium Ferrite

Abstract: SiO 2 -Fe 2 O 3 -CaO (SFC) is believed to be the transition phase during the SiO 2 -Fe 2 O 3 -CaO-Al 2 O 3 (SFCA) formation process. The effect of SiO 2 on the mechanical property and reduction of the CaO-Fe 2 O 3 -SiO 2 system was inspected in this study. Experiments were carried out under air at 1200 • C with different amounts of SiO 2 mixed with Fe 2 O 3 and CaO. The mechanical properties and reduction of samples were studied. Results indicate that the hardness of samples gradually increases with the increa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 26 publications
(27 reference statements)
0
3
0
Order By: Relevance
“…Compared with the results from earlier studies [18][19][20][21][22], this work provides a new view on the determination of mechanical properties. The obtained data are difficult to compare with classical Vickers microhardness, but on the other hand, the values were obtained with an accurate method allowing for rigorous comparison with the future examination of mechanical properties of sinter phases.…”
Section: Factors Influencing the Mechanical Propertiesmentioning
confidence: 78%
See 1 more Smart Citation
“…Compared with the results from earlier studies [18][19][20][21][22], this work provides a new view on the determination of mechanical properties. The obtained data are difficult to compare with classical Vickers microhardness, but on the other hand, the values were obtained with an accurate method allowing for rigorous comparison with the future examination of mechanical properties of sinter phases.…”
Section: Factors Influencing the Mechanical Propertiesmentioning
confidence: 78%
“…In most cases the hardness was measured using Vickers microindentation. However, there are some elementary problems with these measurements, such as too little information about the elastic constants or insufficient size of the crystals, so that the surrounding phases influence the measurements [18][19][20][21][22]. For this reason, in this study SFCA phases were synthesized in the laboratory to attain grain sizes of tens of micrometers, for which the mechanical properties can be quantified using advanced mechanical testing such as nanoindentation.…”
mentioning
confidence: 99%
“…Shi et al [23] and Zhou et al [24] found that with the increase in MgO content, the formation of MgO•Fe 2 O 3 by the reaction between MgO and Fe 2 O 3 increased the formation temperature of the liquid phase in the sinter, resulting in a decrease in the liquid phase content and calcium ferrite mass fraction, which leads to a decrease in the strength of the sinter. Wang et al [25,26] found that increasing the SiO 2 content in the sinter to 4 wt% promoted the formation of calcium ferrite. Further increasing the SiO 2 content caused the formation of silicate, which reduced the contact surface between CaO and Fe 2 O 3 , inhibited the formation of calcium ferrite, and reduced the strength of the sinter.…”
Section: Introductionmentioning
confidence: 99%